2013
DOI: 10.3802/jgo.2013.24.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Utility of serum squamous cell carcinoma antigen levels at the time of recurrent cervical cancer diagnosis in determining the optimal treatment choice

Abstract: ObjectiveTo investigate the utility of serum squamous cell carcinoma antigen (SCC-Ag) levels upon the diagnosis of recurrent cervical cancer for decision making in patient management.MethodsClinical records from 167 cervical cancer patients who developed recurrence between April 1996 and September 2010 were reviewed. A Cox proportional hazards regression model was used to investigate the prognostic significance of serum SCC-Ag levels at the time of recurrence. The effects of various salvage treatments on survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 34 publications
0
25
0
1
Order By: Relevance
“…Some studies have also shown that serum SCC-Ag levels can be adopted for predicting earlier recurrence of cervical cancer. 13,16 Diffusion-weighted imaging is a functional imaging technique that indirectly reflects the microscopic motion of water molecules and the degree of water diffusion in biological tissues and is related to the tissue cellularity and cell membrane integrity. This technique allows the quantification of diffusion by calculating the ADC, and the decrease of ADC values derived from DWI in malignant tumors may be caused by their increased tissue cellularity or cell density and less extracellular space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have also shown that serum SCC-Ag levels can be adopted for predicting earlier recurrence of cervical cancer. 13,16 Diffusion-weighted imaging is a functional imaging technique that indirectly reflects the microscopic motion of water molecules and the degree of water diffusion in biological tissues and is related to the tissue cellularity and cell membrane integrity. This technique allows the quantification of diffusion by calculating the ADC, and the decrease of ADC values derived from DWI in malignant tumors may be caused by their increased tissue cellularity or cell density and less extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…13 Its expression is increased in cervical neoplasms. Serum SCC-Ag is elevated in 28% to 88% of patients with SCC at the time of initial diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, serum SCC-Ag analysis results in earlier recurrence detection in a small proportion (14%) of patients but did not contribute to better survival [11]. On the other hand, another study reported that salvage treatment with radiotherapy or surgery resulted in improved survival compared with chemotherapy or palliative care in patients with serum SCC-Ag levels of less than <14.0 ng/mL at the time of recurrence [12]. …”
mentioning
confidence: 99%
“…L'augmentation du marqueur précédait les symptômes de 5 mois. Néanmoins, au-delà du risque de faux positif avéré, le bénéfice clinique en termes de survie globale est controversé [40,41]. Par ailleurs, le rapport coût−bénéfice n'a pas été réévalué depuis l'avènement de la chimioradiothérapie pelvienne pour les tumeurs localement évoluées.…”
Section: Tep-scanographieunclassified